2017
DOI: 10.1097/nnd.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study on Evidence-Based Nursing Practice in the Contemporary Hospital Setting

Abstract: Evidence indicates that nurses inconsistently engage in evidence-based practice (EBP). This cross-sectional study of 402 nurses at a medical-surgical hospital identifies strategies for augmenting EBP. Nurses' EBP beliefs scores were higher than their EBP implementation scores. Those with baccalaureate/postgraduate degrees had higher EBP beliefs and implementation scores than those with associate degrees or diplomas. Bedside or direct care nurses were less likely to have baccalaureate/higher degrees and had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The results demonstrated that the statistical difference in EBP performance among participants with different educational background, and those with master’ degree reported a higher score in Quick‐EBP‐VIK. This result is in accordance with other studies (Rose Bovino et al, ). Generally, the undergraduate nursing education in most developing countries put more emphasis on professional knowledge and skill, less on the cultivation of students' scientific research ability.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results demonstrated that the statistical difference in EBP performance among participants with different educational background, and those with master’ degree reported a higher score in Quick‐EBP‐VIK. This result is in accordance with other studies (Rose Bovino et al, ). Generally, the undergraduate nursing education in most developing countries put more emphasis on professional knowledge and skill, less on the cultivation of students' scientific research ability.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, teaching of EBP and its related skills are reserved for postgraduate studies (Al Qadire, ). Thus, nurse managers with postgraduate qualifications may have more enthusiasm about EBP and more preparation for EBP (Rose Bovino et al, ). Moreover, our study noted that those who received formal education about EBP in school expressed greater competence of EBP.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cross-sectional studies have examined knowledge, attitude, and practice concerning EBP for nurses [ 31 , 32 ], but few of them have introduced an educational intervention that followed knowledge, attitude, and practice [ 33 , 34 ]. Participants in both the FL and CL groups showed improved knowledge after intervention learning.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients feel the strongest discomfort after anesthesia is not the discomfort caused by the knife but the discomfort caused by the catheter. Patients are always afflicted by it [ 5 ]. In addition to increasing the likelihood of bacterial infections in the urinary system, the catheter also moves early on the patient.…”
Section: Introductionmentioning
confidence: 99%